Loess towards (geo) tourism – proposed application on loess in Vojvodina region (north Serbia) - A. Vasiljević, Djordjije; B. Marković, Slobodan; A. Hose, Thomas; Smalley, Ian; O’Hara-Dhand, Ken; Basarin, Biljana; Lukić, Tin; D. Vujičić, Miroslav (Acta geographica Slovenica, 2011)
Loess-palaeosol sequences preserve the most important continental record of climatic and environmental changes during the Quaternary. As a significant element of global geodiversity and geoheritage, loess-palaeosol sequences could be used as resources for a contemporary trend in sustainable tourism – geotourism. This form of tourism appreciates and promotes non-living nature (geodiversity) through its conservation and interpretation. This further leads to enhancing public awareness of these sites. In this study, we report on a proposal for establishing geotourism at the most important loess sites in the Vojvodina region.